Scale of results in research groups - Freitas, Pablo Fernando Pessoa de (2017)
Purpose: the aim of this paper is to develop a scale to measure results in research groups (RG). Originality/value: the study is innovative in developing a scale for verifying results in Brazilian RG. Its main contribution is data collection from an evaluation made by leaders regarding results that RG’ produced as a whole (meso or organizational level), going further than individual indices of academic productivity. Design/methodology/approach: the scale was developed based on: 1) literature review of empirical papers published between 2005 and 2015 regarding results in RG; and 2) analysis of data (audio recordings, interview transcriptions, field reports) previously collected from RG members, regarding achieved results and re-evaluation of preliminary instruments developed by RG. In total, 387 RG leaders answered the survey after semantic and theoretical analysis by experts and a pre-test. Findings: exploratory factor analysis revealed three factors in the results (Distal Results of External Repercussion, Proximal Research Results and Tangible Research Results), with a total variance of 51.9% explained and reliability indices of α = 0.927, α = 0.872 and α = 0.624, respectively.